Application of Optical Waveguide Technology in AR Glasses - Xiang Weiqiu (MATEC Web of Conferences)
Augmented Reality (AR) glasses have become an important tool for human-computer interaction, and optical waveguide technology plays a key role in the display system of AR glasses. Optical waveguide technology can effectively control light transmission, achieve a large field of view, high light transmittance and excellent image quality. However, the existing waveguide technology still faces challenges such as dispersion control, manufacturing cost and transmittance optimization, and needs to be further researched and optimized. In this paper, the application of optical waveguide technology in AR glasses is reviewed, focusing on its basic principles, key materials, structural design and latest research progress. By analyzing different types of optical waveguides (such as flat waveguides, strip waveguides, etc.) and their grating structure designs, this paper summarizes the advantages and disadvantages of various optical waveguide systems. In addition, the article reviews the latest progress in optical waveguide materials, manufacturing processes and optimized design in recent years, and analyzes the application cases of typical AR glasses products such as Microsoft HoloLens and Magic Leap One. Studies have shown that the development of optical waveguide technology is moving towards high efficiency, low loss, and large-scale manufacturing.